The application of thiazole orange and artificial backbone modifications in the synthesis of fluorescent nucleic acids probes - Klimkowski, P (2019)
Thiazole orange (TO) is an asymmetric cyanine dye used in nucleic acid detection. It has wide applications due to its DNA-intercalating properties, resulting in an “on-off” fluorescent response upon binding to complementary nucleic acids. This thesis describes the use of TO in various fluorescent probe systems.